The critical imagination - Grant, James Eric, 1980- (Oxford philosophical monographs., 2013)
'The Critical Imagination' explores metaphor, imaginativeness and criticism of the arts. James Grant critically examines the idea that art is rewarding because it involves responding imaginatively to a work. He explains the role imaginativeness plays in criticism, and goes on to examine why imaginative metaphors are so common in art criticism.